2008
DOI: 10.1371/journal.pone.0002604
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the Dystrophin-Glycoprotein Complex without Functional Deficits in α-Dystrobrevin Null Muscle

Abstract: α-Dystrobrevin is a component of the dystrophin-glycoprotein complex (DGC) and is thought to have both structural and signaling roles in skeletal muscle. Mice deficient for α-dystrobrevin (adbn−/−) exhibit extensive myofiber degeneration and neuromuscular junction abnormalities. However, the biochemical stability of the DGC and the functional performance of adbn−/− muscle have not been characterized. Here we show that the biochemical association between dystrophin and β-dystroglycan is compromised in adbn−/− s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Exercise tolerance was assessed by using two different methods: a rotating rod device (Rota-Rod, Ugo Basil) (13) and a treadmill Exer 3/6 model (Columbus Instruments) (35). See SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise tolerance was assessed by using two different methods: a rotating rod device (Rota-Rod, Ugo Basil) (13) and a treadmill Exer 3/6 model (Columbus Instruments) (35). See SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Published data indicated that the syntrophin-dystrobrevin complex serves as a linker between dystrophin and membranespanning complex and is important for DAPC stability (34,35). Because elevated levels of myocilin increased the association of ␣1-Syn with dystrophin (Fig.…”
Section: Overexpression Of Myocilin In Vivo Leads To Intracellularmentioning
confidence: 96%
“…5B), we hypothesized that this may increase the association of dystrophin with transmembrane proteins and contribute to the stabilization of the DAPC. To prove this hypothesis, we compared the biochemical stability of dystrophin-dystroglycan interaction using a technique described previously (35). We assessed the levels of dystrophin in the WGA glycoprotein-enriched elutes containing a high concentration of dystroglycans and their associated proteins.…”
Section: Overexpression Of Myocilin In Vivo Leads To Intracellularmentioning
confidence: 99%
“…31) In DAPC, α-DB could help to biochemically stabilize the interaction of dystrophin with the membrane bound dystroglycan complex in skeletal muscle cells and cardiomyocytes. 32,33) DAPC was reported to be associated with cell proliferation pathways including Notch, BMP, and Neuregulin 3 signaling pathways in muscle satellite cells. 34) Dtna N49S may affect the stability of DAPC, which causes the dysregulation of several downstream signaling pathways related to cell proliferation.…”
Section: Dtna Mutation Causes Lvnc In Micementioning
confidence: 99%